Effects of metformin on Sonic hedgehog subgroup medulloblastoma progression: In vitro and in vivo studies - Fang, Huangyi; Wang, Lingfei; Yu, Lisheng; Shen, Fang; Yang, Zelin; Yang, Yue; Li, Shize; Dai, Haipeng; Tan, Feng; Lin, Jian; Sheng, Hansong (Frontiers in Pharmacology, 2022)
Metformin is a first-line drug for type 2 diabetes, and its anticancer effects have also been widely studied in recent years. The Sonic hedgehog (Shh) signaling pathway is involved in the initiation and progression of medulloblastoma. In order to develop a new treatment strategy for medulloblastoma (MB), this study investigated the inhibitory effect of metformin on MB and the underlying mechanism of metformin on the Shh signaling pathway. The effect of metformin on proliferation was evaluated by cell counting kit 8 (cck-8) test and colony formation experiment. The effect of metformin on metastasis was assessed by scratch-wound assay and transwell invasion assay. Cell cycle and apoptosis were evaluated by flow cytometry, and the associated proteins were exam¬ined by western blotting. The mRNA and protein expression levels related to the Shh pathway were measured by quantitative PCR, western blotting and immunofluorescence staining. Xenograft murine model was carried out to evaluate the anticancer effect of metformin on medulloblastoma in vivo. Metformin inhibited proliferation and metastasis of the Shh subgroup MB cell line, and the inhibitory effect on proliferation was related to apoptosis and the block of the cell cycle at G0/G1 phase. Animal experiments showed metformin inhibits medulloblastoma growth in vivo. Moreover, metformin decreased mRNA and protein expression levels of the Shh pathway, and this effect was reversed by the AMP activated protein kinase (AMPK) siRNA. Furthermore, the pro-apoptotic and cell-cycle arrest effects of metformin on Daoy cells could be reversed by Shh pathway activators. Our findings demonstrated that metformin could inhibit medulloblastoma progression in vitro and in vivo, and this effect was associated with AMPK-mediated inhibition of the Shh signaling pathway in vitro studies.